2012
DOI: 10.1097/opx.0b013e318244e487
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Upper and Lower Lids' Meibomian Gland Morphology, Tear Film, and Dry Eye

Abstract: MG scores between lids were significantly different but correlated. MG loss was significantly correlated to tear film characteristics including lipid layer thickness and stability. MG thickness and bent angle of the UL were related to NIBUT. The combination of both lids' MG loss showed best predictive ability of dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
118
5
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 29 publications
16
118
5
4
Order By: Relevance
“…The gland detection algorithm are then applied to the identified region. Although this process of drawing out gland region manually may appear similar to what has already been done in previous studies, [5][6][7]9 the important difference is that here the region inside the identified area is subjected to gland detection by the algorithm, whereas in previous studies the area of interest are drawn by the user with the intention of locating the glands.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The gland detection algorithm are then applied to the identified region. Although this process of drawing out gland region manually may appear similar to what has already been done in previous studies, [5][6][7]9 the important difference is that here the region inside the identified area is subjected to gland detection by the algorithm, whereas in previous studies the area of interest are drawn by the user with the intention of locating the glands.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to gland length and width, meibomian glands can also be characterized by other morphological features such as shape, contour, and tortuosity. [5][6][7]9 Such features are important when grading images that are intermediate between the healthy and unhealthy ones. A limitation of the current study is that these features were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations